(untitled) (Journal of the College of Basic Education, 2022)
The geology of the study area covers the sediments of the Quaternary time and consists of the Pleistocene deposits represented by the sediments of the river terraces of the Euphrates River and the Holocene sediment represented by the sediments of the floodplain, the sediments that fill the valleys, the deposits that fill the depressions, and the sediments resulting from human activities.The dry climate of the study area was characterized by high temperatures in summer and low in winter, and winter rains that affected the groundwater, as there is an increase in the level of groundwater during the winter period and a decrease in the summer. The research dealt with the physical and chemical properties of the waters of Abu Ghraib and Saqlawiya, the study area, physical properties such as water temperature, turbidity, total salts, electrical conductivity, and chemical properties such as pH, sulfates, chlorides and nitrates.